PENINGKATAN MUTU PEMBELAJARAN GERAK DASAR TARI KELAS VII MELALUI VIDEO ANIMASI 2D MENGGUNAKAN METODE ADDIE - Dede Iriyanto; Nana Suarna; Raditya Danar Dana Raditya Danar Dana (ITP Press, 2023)
The Merdeka Curriculum places Dance as a subject that is given at the junior high school level (SMP) class VII at SMPN 1 Gunung Jati. The quality of dance learning is influenced by educational components in improving the quality of learning, one of which is by utilizing learning media. The subjects in the study were class VII students at SMPN 1 Gunung Jati who took the subject of Dance. The problems so far include; (1) Learning media for basic dance movements is difficult to display motion and sound in print media pages, (2) The impact of increasing the implementation of dance learning media with 2D animation videos. The purpose of this research is; 1) To display learning media for basic dance movements with 2D animation and sound, (2) To find out the increase in the implementation of dance learning media with 2D animation video.. This research method uses the ADDIE method which has 5 stages, namely: Analysis, Design, Development, Implementation and Evaluation. ADDIE is a research method that is suitable for developing learning media because it is product oriented so it is suitable for developing 2D animated videos as learning media. The results of the normality test (Shapiro-Wilk) show a significant value of 0.082, this indicates that the results of the normality test have a significant value of more than 0.05. Therefore H0 is accepted, so that the application of 2D animation learning media has an impact on improving the quality of learning.